If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+2(2v+-2)=-5(3v-1)+v
We move all terms to the left:
1+2(2v+-2)-(-5(3v-1)+v)=0
We add all the numbers together, and all the variables
2(2v-2)-(-5(3v-1)+v)+1=0
We multiply parentheses
4v-(-5(3v-1)+v)-4+1=0
We calculate terms in parentheses: -(-5(3v-1)+v), so:We add all the numbers together, and all the variables
-5(3v-1)+v
We add all the numbers together, and all the variables
v-5(3v-1)
We multiply parentheses
v-15v+5
We add all the numbers together, and all the variables
-14v+5
Back to the equation:
-(-14v+5)
4v-(-14v+5)-3=0
We get rid of parentheses
4v+14v-5-3=0
We add all the numbers together, and all the variables
18v-8=0
We move all terms containing v to the left, all other terms to the right
18v=8
v=8/18
v=4/9
| 23=-5w+3(w+3) | | 6/8x+12=84 | | 40r=91 | | 3x+2+4x=5x+8 | | -10x+100=20 | | 5x+16=6x-12 | | 16+5m=-5-8(7m+5) | | Y-16-13y=1 | | 36^a=4 | | 14x+1=8x+13 | | -171=4(1+5a)+5a | | -x/10+3=-10 | | -2r+34=-6+2(4r+5) | | 3y+48=8y-47 | | (3x+1)+x=7 | | 4x-1+12x-17=0 | | -5(v-3)=39-2v | | 105=5(1+3x)-5 | | (2x+5)=39 | | 9=x+5+1 | | p=13+1/11 | | 1.4h+30+35=436.60 | | 50+2=7y | | 2-7n+6n=1 | | 9x^2-12x+4=x+8 | | 12y+8=9y+41 | | p=144/11 | | -4×-3=-6x+9 | | 1.4r+30=35 | | 4x+6=x÷2 | | -5a+5a=-1 | | (7+13x)(-20+16x)=x |